Abnormal subchondral trabecular bone remodeling in knee osteoarthritis under the influence of knee alignment. Issue 1 (January 2022) - Han, Xuequan; Cui, Junqi; Chu, Linyang; Zhang, Weituo; Xie, Kai; Jiang, Xu; He, Zihao; Du, Jingke; Ai, Songtao; Sun, Qi; Wang, Liao; Wu, Haishan; et al.
Summary: Objective: This study aimed to investigate the abnormal subchondral trabecular bone (STB) remodeling in knee osteoarthritis (OA) under the influence of knee alignment [hip-knee-ankle (HKA) angle]. Design: Forty-one patients with knee OA underwent radiographic examination before total knee arthroplasty (TKA) for the measurement of HKA angle. Tibial plateau specimens obtained during TKA were used for histomorphometric analyses to assess STB remodeling and cartilage degradation. Tartrate-resistant acidic phosphatase (TRAP) staining was used to test osteoclast activity. Osterix, osteocalcin, and sclerostin expression in the STB were determined using immunohistochemistry. Results: The interaction between HKA angle and side (medial vs lateral of tibial plateau) was the main significant influence factor for STB remodeling and microstructure. The STB with the deviation of the knee alignment was accompanied by obvious abnormal bone remodeling and microstructural sclerosis. Bone volume fraction (BV/TV) was the only significant influence factor for OARSI score, the larger the BV/TV of STB, the higher the OARSI score of cartilage. Moreover, the tibial plateau affected by alignment had more TRAP + osteoclasts, Osterix + osteoprogenitors, and osteocalcin + osteoblasts and fewer sclerostin + osteocytes. Conclusions: The variation of tibial plateau STB remodeling activity and microstructure was associated with HKA angle and cartilage degradation. Knee malalignment may cause abnormal STB remodeling and microstructural sclerosis, which may potentially affect load stress transmission from the cartilage to the STB, thus resulting in accelerated knee OA progression.